2016
DOI: 10.1098/rstb.2015.0429
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of neural circuit function in Alzheimer's disease

Abstract: An essential feature of Alzheimer's disease (AD) is the accumulation of amyloid-β (Aβ) peptides in the brain, many years to decades before the onset of overt cognitive symptoms. We suggest that during this very extended early phase of the disease, soluble Aβ oligomers and amyloid plaques alter the function of local neuronal circuits and large-scale networks by disrupting the balance of synaptic excitation and inhibition ( E / I balance) in the brain. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
240
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(263 citation statements)
references
References 64 publications
9
240
0
Order By: Relevance
“…feature in AD-like mouse models and in humans with early-stage AD, underlying behavior-relevant local and long-range circuit dysfunctions (14)(15)(16). Our experiments demonstrated that treatment with NB-360 effectively abolished excess neuronal activity in transgenic mice (Fig.…”
Section: Significancesupporting
confidence: 52%
“…feature in AD-like mouse models and in humans with early-stage AD, underlying behavior-relevant local and long-range circuit dysfunctions (14)(15)(16). Our experiments demonstrated that treatment with NB-360 effectively abolished excess neuronal activity in transgenic mice (Fig.…”
Section: Significancesupporting
confidence: 52%
“…Studies have shown that a disrupted E/I balance can cause network dysfunction and various diseases (Fernandez et al, 2007; Kehrer et al, 2008; Gogolla et al, 2009), including AD (Schmitt, 2005; Rissman and Mobley, 2011; Busche and Konnerth, 2016). Therefore, after examining the excitatory and inhibitory currents separately in pyramidal cells, we also wanted to check whether the E/I balance is altered in App NL-F mice.…”
Section: Resultsmentioning
confidence: 99%
“…The pathologic hallmarks of AD include amyloid β (Aβ) plaques, neurofibrillary tangles (NFTs), and neuronal degeneration (Serrano-Pozo et al, 2011). Meanwhile, neuronal hyperactivity, network hyperexcitability, and spontaneous epileptiform activity have been observed in human amyloid precursor protein (hAPP) transgenic mouse models with high levels of Aβ (Palop et al, 2007, 2011; Busche et al, 2008; Palop and Mucke, 2009; Harris et al, 2010; Roberson et al, 2011; Yan et al, 2012; Busche and Konnerth, 2016). Hypersynchronous network activity, also observed in AD patients (Lam et al, 2017), may further contribute to the emergence of AD symptoms such as cognitive impairment in early stages of the disease (Noebels, 2011; Bakker et al, 2012; Scharfman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The topic of amyloidogenesis has been the subject of many scientific endeavors and a great variety of papers have been published, approaching the problem from all possible angles: diagnostics [63][64][65][66], therapeutic [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] and structural/molecular [82][83][84][85]. Our publication does not, however, discuss amyloidogenesis as such, but rather the molecular processes which lead to the formation of fibrillary aggregates commonly referred to as amyloids.…”
Section: Discussionmentioning
confidence: 99%